Simulation study On PCU ... [et al.] / [mikrofilem] - 255474 Chew, Huat Chiang (Skudai : Universiti Teknologi Malaysia, 1999)
Project paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1999